2004
DOI: 10.1051/0004-6361:20034600
|View full text |Cite
|
Sign up to set email alerts
|

Extragalactic large-scale structures behind the southern Milky Way

Abstract: Abstract. As part of our efforts to unveil extragalactic large-scale structures behind the southern Milky Way, we here present redshifts for 764 galaxies in the Hydra/Antlia, Crux and Great Attractor region (266 . A total of 947 galaxies have been observed, a small percentage of the spectra (N = 109, 11.5%) were contaminated by foreground stars, and 74 galaxies (7.8%) were too faint to allow a reliable redshift determination. With MEFOS we obtained spectra down to the faintest galaxies of our optical galaxy su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 27 publications
6
47
0
Order By: Relevance
“…As the Norma cluster has also been proposed as the possible center of a "Great Attractor" region (Woudt et al 2003, Kolatt et al 1995, this large angular separation supports the idea that the SBF-GA and the ZOA-GA might be different substructures within a generally overdense region of the universe.…”
Section: The Great Attractor Acting Upon Hydra and Centaurussupporting
confidence: 63%
“…As the Norma cluster has also been proposed as the possible center of a "Great Attractor" region (Woudt et al 2003, Kolatt et al 1995, this large angular separation supports the idea that the SBF-GA and the ZOA-GA might be different substructures within a generally overdense region of the universe.…”
Section: The Great Attractor Acting Upon Hydra and Centaurussupporting
confidence: 63%
“…It is distinct from the much flatter distribution of the H i-survey undertaken under the same observing conditions for the Hydra/Antlia survey area (top panel of inset; as in Paper I). This is in agreement with the results by Woudt et al (2004) who have shown that the velocity distribution of all survey galaxies for which we obtained redshifts (about 15% on average for the deep ZOA surveys, mostly optical spectra from our dedicated follow-up surveys at the SAAO and ESO, plus some previously published redshifts), is fairly flat out to 20 000 km s −1 in the Hydra/Antlia region, while the Crux region and -much more pronounced -the GA region show a distinct broad peak of galaxies at ∼4000−5000 km s −1 (see their Fig. 5), while the histogram is otherwise similar for the three survey regions.…”
Section: Velocity Distribution and Detection Ratesupporting
confidence: 94%
“…The extent and shape of this wall was suspected in earlier papers (e.g., Kraan-Korteweg et al 1994) and strongly supported in more recent work (Woudt et al 2004;Kraan-Korteweg 2005;Ebeling et al 2005;Radburn-Smith et al 2006). A sketch of this Wall, as well as the Centaurus filament, is given with Fig.…”
Section: Sky Projectionssupporting
confidence: 68%
See 1 more Smart Citation
“…It is also the sixth brightest cluster in ROSAT All-Sky Survey and the second brightest non-cool-core cluster after Coma (Böhringer et al 1996). ESO 137-001 is a blue emission-line galaxy (Woudt et al 2004) that is only ∼180 kpc from the cluster's X-ray peak in projection. Its radial velocity (4680 ± 71 km s −1 ; Woudt et al 2004) is close to the average velocity in A3627 (4871 ± 54 km s −1 ; Woudt et al 2008), so most of its motion is probably in the plane of sky.…”
Section: No 2 2010 Spectacular X-ray Tails Intracluster Star Formamentioning
confidence: 99%